TONOPLAST NA+/H+ ANTIPORT ACTIVITY AND ITS ENERGIZATION BY THE VACUOLAR H+-ATPASE IN THE HALOPHYTIC PLANT MESEMBRYANTHEMUM-CRYSTALLINUM L - Barkla, B; Zingarelli, L; Blumwald, E; Smith, J (1995)
Tonoplast vesicles were isolated from leaf mesophyll tissue of the inducible Crassulacean acid metabolism plant Mesembryanthemum crystallinum to investigate the mechanism of vacuolar Na+ accumulation in this halophilic species. In 8-week-old plants exposed to 200 HIM NaCI for 2 weeks, tonoplast H+-ATPaSe activity was approximately doubled compared with control plants of the same age, as determined by rates of both ATP hydrolysis and ATP-dependent H+ transport. Evidence was also obtained for the presence of an electroneutral Na+/H+ antiporter at the tonoplast that is constitutively expressed, since extravesicular Na+ was able to dissipate a pre-existing transmembrane pH gradient. Initial rates of H+ efflux showed saturation kinetics with respect to extravesicular Na+ concentration and were 2.1-fold higher from vesicles of salt-treated plants compared with the controls. Na+-dependent H+ efflux also showed a high selectivity for Na+ over K+, was insensitive to the transmembrane electrical potential difference, and was more than 50% inhibited by 200 μM N-amidino-3,5-diamino-6-chloropyrazine-carboxamide hydrochloride. The close correlation between increased Na+/H+ antiport and H+-ATPase activities in response to salt treatment suggests that accumulation of the very high concentrations of vacuolar Na+ found in M. crystallinum is energized by the H+ electrochemical gradient across the tonoplast.